PRIMARY CNS LYMPHOMA MASQUERADING AS TUMEFACTIVE DEMYELINATION. Issue 11 (9th October 2013) - Ellawela, Shan; Joseph, Robin; Kulla, Andres; O'Leary, Colin
Abstract : A 47 year old female presented with sub–acute cognitive decline and personality change, without any significant focal neurology. An MRI scan showed extensive white matter signal change and oedema with a few enhancing focal lesions and minimal mass effect. The radiological differential diagnosis consisted of primary CNS tumour/Lymphoma, Demyelination and CNS vasculitis. Oligoclonal bands were only detected in CSF, but numerous other investigations turned out to be unhelpful. An image guided, burr–hole brain biopsy of the most prominent and enhancing left frontal lesion, showed non–specific reactive changes, which proved to be non–diagnostic. Patient declined a repeat biopsy. Subsequently she was treated with high dose pulsed steroids and showed a marked clinical improvement. Initial follow up imaging showed some radiological improvement and she remained clinically stable over the ensuing months. Serial imaging there after, continued to show a chaotic background, with regression of earlier lesions and appearance of new lesions. There was also a changing enhancement pattern of some of the existing lesions. During this period she only had a single episode of right leg weakness, gait ataxia and intermittent visual impairment. This too responded well to a course of high dose steroids. An aggressive, multifocal, tumefactive demyelinating process was thought to be the most likely diagnosis at this stage. She was then commenced on Natalizumab, nearly a year after her first presentation. After two doses of Natalizumab, she presented acutely with left sided focal motor seizures and a left hemiparesis. Neuroimaging at this stage showed clear radiological deterioration. A repeat brain biopsy was again declined by the patient. Following a further dose of Natalizumab and continuing clinical and radiological progression, an open brain biopsy was finally carried out. This showed a high grade B–cell Non Hodgkin Lymphoma. She has since been commenced on intrathecal Methotrexate and also underwent whole brain radiotherapy. This is an example of a Primary CNS lymphoma behaving initially as an aggressive tumefactive demyelination, both clinically and radiologically. It also illustrates the difficulties of getting a definitive diagnosis, despite appropriate investigations, which in this case included multiple brain imaging and a brain biopsy.